2011
DOI: 10.1103/physrevb.83.224202
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of disorder, classical and quantum vibrational contributions to atomic mean-square amplitudes in dielectric pentachloronitrobenzene

Abstract: The solid-state molecular disorder of pentachloronitrobenzene (PCNB) and its role in causing anomalous dielectric properties are investigated. Normal coordinate analysis (NCA) of atomic mean-square displacement parameters (ADPs) is employed to distinguish disorder contributions from classical and quantum-mechanical vibrational contributions. The analysis relies on multitemperature (5-295 K) single-crystal neutron-diffraction data. Vibrational frequencies extracted from the temperature dependence of the ADPs ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…The reduced VDOS, g()/ 2 , shown in the inset, is consistent with the presence of a weak feature or "boson peak" centered at about 2 meV superimposed to the Debye VDOS, g()   2 . It is worth mentioning that the crystal nature of the material enables an unambiguous identification of features appearing in g() to discrete normal modes and in fact, the observed extrema match the librational frequencies derived from the normal mode analysis of the atomic displacements [40], yielding 4.26 meV, 5.36 meV and 5.98 meV, as well as a peak at 8.55 meV assigned to molecular torsional oscillations.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…The reduced VDOS, g()/ 2 , shown in the inset, is consistent with the presence of a weak feature or "boson peak" centered at about 2 meV superimposed to the Debye VDOS, g()   2 . It is worth mentioning that the crystal nature of the material enables an unambiguous identification of features appearing in g() to discrete normal modes and in fact, the observed extrema match the librational frequencies derived from the normal mode analysis of the atomic displacements [40], yielding 4.26 meV, 5.36 meV and 5.98 meV, as well as a peak at 8.55 meV assigned to molecular torsional oscillations.…”
supporting
confidence: 57%
“…Here we study a minimally disordered crystalline system in which only a few degrees of freedom make it to depart from a fully ordered state. The chosen system is a quasiplanar hexasubstituted benzene derivative, pentachloronitrobenzene (PCNB, C 6 Cl 5 NO 2 ), that exhibits a layered structure of rhombohedral (space group 3 R ) parallel planes in which the molecules can rotate around a six-fold-like axis [21,[39][40][41][42]. Nevertheless, the molecular dipole has two nonzero (in-plane and a small out-of-plane) components with a highly anisotropic dynamical coupling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T1 shows the refinement results from Cole et al (2011), where LAUENORM was used for normalization and merging, while LAUE4 was used for refinements T2-T5. T1-T3 use the integrated intensities from the published refinement, which were calculated using an earlier version of ARGONNE_ BOXES, while T4 and T5 use integrated intensities calculated by a newer version of ARGONNE_BOXES.…”
Section: Discussionmentioning
confidence: 99%
“…The final comparison is VIVALDI data for a 5 K data set for pentachloronitrobenzene from Cole et al (2011), shown in Table 3 and Fig. 6.…”
Section: Refinementmentioning
confidence: 99%